Prophylaxis of thrombotic and embolic events in acute ischemic stroke with the low-molecular-weight heparin Certoparin - Diener, Hans-Christoph; Ringelstein, Erich B.; Kummer, Rüdiger von; Landgraf, Helmut; Koppenhagen, Klaus; Harenberg, Job; Rektor, Ivan; Csányi, Attila; Schneider, Dietmar; Klingelhöfer, Jürgen; Brom, Joachim; Weidinger, Gottfried (Stroke, 2006)
Background and Purpose— Patients with stroke are at substantial risk of thromboembolic complications and therefore require antithrombotic prophylaxis. To show the noninferiority of the low-molecular-weight heparin certoparin to unfractionated heparin (UFH) for the prevention of thromboembolic complications, we performed a randomized, double-blind, active-controlled multicenter trial in patients with acute ischemic stroke. - - Methods— Overall, 545 patients were randomized within 24 hours of stroke onset to treatment with certoparin (3000 U anti-Xa OD; n=272) or UFH (5000 U TID; n=273) for 12 to 16 days. Patients with paresis of a leg and an National Institutes of Health Stroke Scale score of 4 to 30 points were included. The primary end point was a composite outcome of proximal deep vein thrombosis, pulmonary embolism, or death related to venous thromboembolism during treatment. Computed tomography was performed at trial entry, after 7 days, and when clinical deterioration occurred. - - Results— The per-protocol analysis revealed 17 (7.0%) primary events in the certoparin group compared with 24 (9.7%) in the UFH group, thereby demonstrating noninferiority (P=0.0011), confirmed by intention-to-treat analysis (6.6% versus 8.8%; P=0.008). Major bleeding occurred during treatment in 3 patients allocated to certoparin (1.1%) and 5 patients allocated to UFH (1.8%). - - Conclusions— Certoparin (3000 U anti-Xa OD) is at least as effective and safe as UFH (TID) for the prevention of thromboembolic complications in patients with acute ischemic stroke.